Design and equipment for restaurants and foodservice : a management view - Katsigris, Costas; Thomas, Chris (New Jersey : John Wiley & Son, Inc., 2006)
Focusing on the design and equipment of restaurants and foodservice facilities, this book offers coverage of site selection and the changing diversity of restaurants and mixed theme facilities. It reflects the trends in design and the equipment technologies.
Chapter 1. Economics of Site Selection -- Chapter 2. Restaurant Atmosphere and Design -- Chapter 3. Principles of Kitchen Design -- Chapter 4. Space Allocation -- Chapter 5. Electricity and Energy Management -- Chapter 6. Gas, Steam, and Water -- Chapter 7. Design and Environment -- Chapter 8. Safety and Sanitation -- Chapter 9. Buying and Installing Foodservice Equipment -- Chapter 10. Storage Equipment: Dry and Refrigerated -- Chapter 11. Preparation Equipment: Ranges and Ovens -- Chapter 12. Preparation: Equipment: Fryers and Fry Stations -- Chapter 13. Preparation Equipment: Broilers, Griddles, and Tilting Braising Pans -- Chapter 14. Steam Cooking Equipment -- Chapter 15. Cook-Chill Technology -- Chapter 16. Dishwashing and Waste Disposal -- Chapter 17. Miscellaneous Kitchen Equipment -- Chapter 18. Smallware for Kitchens -- Chapter 19. Tableware -- Chapter 20. Linens and Tables Coverings.
Includes index.
Keywords: FOOD SERVICE MANAGEMENT